PHONETIC ANALYSIS OF SANSKRIT BORROWINGS IN THE UZBEK LANGUAGE - PhD. Jumaniyazova Dilnoza Alimboevna (UrSU) (Scholar Express Journal, 2023)
This article deals with the analysis of phonetic adaptation features of Sanskrit words that played a certain role in the enrichment of the vocabulary of the Uzbek language
Keywords: Sanskrit borrowings; phonetic change; positional and combinatorial changes